Design of Wind Turbine types for Hybrid Power System in Bawean Island - Indah Noor Dwi Kusuma Dewi (Fakultas Teknik, 2018)
Today the electricity supply to Bawean region is at least 8,000 families not yet gotten by electricity. The primary load needed is 2.8 MWh /day with peak load of 454 kW. A software tool, the Hybrid Optimization Model for Electric Renewables ( HOMER ) is used for the analysis. In this project, the HOMER analysis focused on the type of wind turbine that will be used and then the results were compared based on the total NPC, COE, excess electricity generated and renewable fraction. The Wind turbine types selected are BWC Excel R (DC), Synergy S3000 (DC), Synergy S20000 (DC), Synergy S5000DD (DC), Jacobs 29-20 (AC), Fuhrlander 250 (AC) and Fuhlander 30 (AC ).Keywords : turbine, hybrid, HOMER, Bawean